Thm 2: Suppose m, n eN are such that n >=m. Then n = m + b if and only if b = n -m.

THe problem:

If n, m e N with n >= m and n - m = 0, then n = m.

I am asked to prove this as a consequence of Thm. 2. Any adivce? THanks.

Printable View

- Feb 16th 2009, 10:02 PMjzelltProof help: equality of natural numbers
Thm 2: Suppose m, n eN are such that n >=m. Then n = m + b if and only if b = n -m.

THe problem:

If n, m e N with n >= m and n - m = 0, then n = m.

I am asked to prove this as a consequence of Thm. 2. Any adivce? THanks.

- Feb 16th 2009, 10:03 PMChris L T521